EFEKTIVITAS PEMBERDAYAAN PEREMPLIAN : EWALUASI KEBERHASILAN PENGORGANISASIAN MASYARAKAT DALAM PEMBERIDAYAAN EKONOMI KELUARGA DI DESA LOYANG KABUPATEN INDRAMAYU (Sosio Konsepsia, 2010)
This articles discusses the effectivity of women empowerment programme implementation. The discussion is focussed on two aspects: the role of empowering women, and the changing economic condition of those engaged as member of that institution. In the aspect of community organization as a method of social work, there was found positive support of the local community. As the consequently, the social institution had been estabilished. The role of this institution is aplace for empowering the vulnerable women to social economic condition. Three years after that empowerment programme implementation from 35 samples of respondents showed that : 68,57 % of them were able to increase their monthly income, 28,57 % just the same as before, and the contrary only 2,86 % of them decreased.The percentage of that increased ranged betwen 20 % and 150 %, and mean 97,92 %. From teh economic point of view, the non parametic statistic different lest showed that there were a significant increased of their monthly income. Nevertheless, according to the standard of poverty level in that local area, 60% of theme were remained below of that standard.It was concluded that the community organization was effective to increase family income, and women had power to support family economy. However, in order to release them ot of poverty, the programme continuity and coordination among other sectors were neede.